2000
DOI: 10.1080/09500830010003830
|View full text |Cite
|
Sign up to set email alerts
|

When does a crystal conduct heat like a glass?

Abstract: Semiconducting crystalline materials that are poor conductors of heat are important as thermoelectric materials and for technological applications involving thermal management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 7 publications
(8 reference statements)
1
34
0
Order By: Relevance
“…The low thermal conductivity measured in these compounds is due to the weak guest-host electronic interactions, which leads to strong coupling between the localized guest rattler vibrations and the host acoustic modes. This interpretation is consistent with transport [11][12][13][14][15][16][17][18], Raman scattering [19] and acoustic measurements [20,21] as well as with theoretical calculations [22,23]. Several theoretical studies of the electronic, structural, and vibrational properties of both the pure Type I clathrate materials and various compounds based on the Type I lattice structure have also been carried out [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionsupporting
confidence: 67%
“…The low thermal conductivity measured in these compounds is due to the weak guest-host electronic interactions, which leads to strong coupling between the localized guest rattler vibrations and the host acoustic modes. This interpretation is consistent with transport [11][12][13][14][15][16][17][18], Raman scattering [19] and acoustic measurements [20,21] as well as with theoretical calculations [22,23]. Several theoretical studies of the electronic, structural, and vibrational properties of both the pure Type I clathrate materials and various compounds based on the Type I lattice structure have also been carried out [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionsupporting
confidence: 67%
“…3,4 Quantum tunneling of guest atoms has been a very important issue to understand the physical properties of clathrates. [5][6][7][8][9][10] For Eu clathrates, quantum tunneling at ϳ450 MHz frequency among the four equivalent sites was discussed from the viewpoint of Mössbauer experiments. 5 The mixed state of thermal rattling and tunneling are argued using raman spectroscopy in the Ge clathrate family.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15] In this respect well-tested models of thermal vibrations and lattice dynamics in solids have had a remarkable comeback. 16,17 By applying the Debye model, Sales and co-workers have shown that even the most basic crystallographic parameter, the average isotropic mean square displacement parameter (͗U 2 ͘) for the framework atoms, can provide a quite accurate estimate of the thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%